Carcinoma of the gastroesophageal junction in Chinese patients - Huang, Qin (Baishideng Publishing Group Co., Limited, 2012)
Carcinoma of the gastroesophageal junction (GEJ) is defined as carcinoma that crosses the GEJ line, irrespective of where the tumor epicenter is located. This group of cancer is rare but controversial. Based on study results from the majority of epidemiologic and clinicopathologic investigations carried out in Western countries, this cancer is believed to arise from Barrett’s esophagus (BE) and includes both distal esophageal and proximal gastric carcinomas because of similar characteristics in epidemiology, clinicopathology, and molecular pathobiology in relation to BE. As such, the most recent American Joint Committee on Cancer staging manual requires staging all GEJ carcinomas with the rule for esophageal adenocarcinoma (EA). This mandate has been challenged recently by the data from several studies carried out mainly in Chinese patients. The emerging evidence derived from those studies suggests: (1) both BE and EA are uncommon in the Chinese population; (2) almost all GEJ cancers in Chinese arise in the proximal stomach and show the features of proximal gastric cancer, not those of EA; (3) application of the new cancer staging rule to GEJ cancer of Chinese patients cannot stratify patients’ prognosis effectively; and (4) prognostic factors of GEJ cancer in Chinese are similar, but not identical, to those of EA. In conclusion, the recent evidence suggests that GEJ cancer in Chinese shows distinct clinicopathologic characteristics that are different from EA. Further investigations in molecular pathology may help illustrate the underlying pathogenesis mechanisms of this cancer in Chinese patients and better manage patients with this fatal disease.